Circulating microbial small RNAs are altered in patients with rheumatoid arthritis. Issue 12 (21st September 2020) - Ormseth, Michelle J; Wu, Qiong; Zhao, Shilin; Allen, Ryan M; Solus, Joseph; Sheng, Quanhu; Guo, Yan; Ye, Fei; Ramirez-Solano, Marisol; Bridges, S Louis; Curtis, Jeffrey R; Vickers, Kasey; et al.
Abstract : Objectives: To determine if plasma microbial small RNAs (sRNAs) are altered in patients with rheumatoid arthritis (RA) compared with control subjects, associated with RA disease-related features, and altered by disease-modifying antirheumatic drugs (DMARDs). Methods: sRNA sequencing was performed on plasma from 165 patients with RA and 90 matched controls and a separate cohort of 70 patients with RA before and after starting a DMARD. Genome alignments for RA-associated bacteria, representative bacterial and fungal human microbiome genomes and environmental bacteria were performed. Microbial genome counts and individual sRNAs were compared across groups and correlated with disease features. False discovery rate was set at 0.05. Results: Genome counts of Lactobacillus salivarius, Anaerobaculum hydrogeniformans, Staphylococcus epidermidis, Staphylococcus aureus, Paenisporosarcina spp, Facklamia hominis, Sphingobacterium spiritivorum, Lentibacillus amyloliquefaciens, Geobacillus spp, and Pseudomonas fluorescens were significantly decreased in the plasma of RA compared with control subjects. Three microbial transfer RNA-derived sRNAs were increased in RA versus controls and inversely associated with disease activity. Higher total microbial sRNA reads were associated with lower disease activity in RA. Baseline total microbial sRNAs were threefold higher among patients who improved with DMARD versus those who did not but did not change significantly after 6 months of treatment. Conclusion: Plasma microbial sRNA composition is altered in RA versus control subjects and associated with some measures of RA disease activity. DMARD treatment does not alter microbial sRNA abundance or composition, but increased abundance of microbial sRNAs at baseline was associated with disease activity improvement at 6 months.